Magnetron Sputtering vs. Electrodeposition for Hard Chrome Coatings: A Comparison of Environmental and Economic Performances - Merlo, Antoine (Materials (Basel), 2021)
The coating of materials with specific films is widely used to improve material properties and many technologies exist to perform it. In the last few years, the replacement of wet electrodeposition processes has been continuously encouraged in the EU due to the problematic waste management linked to those processes. In this paper, magnetron sputtering is studied as an alternative to conventional electrodeposition by comparing the technologies’ environmental impacts and costs. From the study, it appears that while magnetron sputtering greatly reduces hexavalent chromium emissions over the production, it has an increased electricity consumption mostly due to its lower production capacity, thus leading to more greenhouse gas emissions. Furthermore, a short discussion on the quantification of the impact of hexavalent chromium emissions is conducted. Regarding costs, the electrodeposition process has a lower cost of investment and of consumables, but requires more work time for the different steps of the process, making the total price per functional unit roughly equal. However, the cost per functional unit strongly depends on assumptions on the required work time, for which a sensitivity study is performed. Finally, the impacts of these two competing coating processes are discussed to complete the technological comparison for the case of hard chromium deposition.